Free love : a novel - Hadley, Tessa (Harper, an imprint of Harper Collins Publishers, 2022)
when the twenty-something son of an old friend pays the Fischers a visit one hot summer evening, and kisses Phyllis in the dark garden after dinner, something in her catches fire. Newly awake to the world, Phyllis makes a choice that defies all expectations of her as a wife and a mother. Nothing in these ordinary lives is so ordinary after all, it turns out, as the family’s upheaval mirrors the dramatic transformation of the society around them... --